Migration of Talent: Foreign Students and Graduate Economics Education in the United States - Milind Rao (Levy Economics Institute of Bard College, 1993)
In this paper, Rao tackles the reasons behind the increasing number and share of foreign students enrolled in Ph.D. economics programs in the U.S. The conventional argument of comparative advantage in U.S. graduate economics education fails to stand up under closer scrutiny. In addition to not explaining the actual and relative decline of American students pursuing graduate economics education, the traditional view fails to explain the relatively narrow scope of foreign students in these programs: The majority of foreign students come from a few Asian countries (e.g., India, South Korea, China, and Taiwan). Among the questions posed in this paper are the reasons for the change in the proportion of foreign students over time, and the effect of this change on American graduate (and undergraduate) economics education. It is surmised that most foreign students enroll in American Ph.D. programs to facilitate their migration to this country. Given the relative ease of securing work permission as a university faculty member-for which a U.S. Ph.D. is essential-most foreign students view an American Ph.D. and a subsequent academic job as an ideal entree to the U.S. In contrast, the most popular postgraduate path for American college economics majors is business or law school, and the appropriate strategy for these institutions is to offer a curriculum that fosters successful completion of an M.B.A. or J.D. via a general rather than a specialized economics training. Meanwhile, Rao ponders the possibility of "reverse foreign aid" occurring: After all, the home governments of these students are not compensated for their education subsidies through the undergraduate level. In sum, he suggests that the influx of foreign Ph.D. students-who typically receive financial aid from U.S. institutions-must be considered as a positive phenomenon. Since most of these students remain in the U.S. and become part of the vital stock of human capital, the financial aid awarded them should be regarded as an investment in a productive asset.
Keywords: 330